MOTOR PROFILE OF CHILDREN WITH AGE FROM 9 TO 10 YEARS OLD IN A PUBLIC SCHOOL IN THE CARATATEUA/PA ISLAND (Fiep Bulletin - online, 2011)
This study has as focus of interest the Motor Development (MD), of children between 9 and 10 years old. To measured this work, it was necessary to use a test that involves the ample motor coordination. This test was proposed by Ulrich (2000) and authenticated in Brazil with a gaucha people by Valentini (2008), it was named Test of Gross Motor development Second Edition (TGMD-2). In order to carry out this research, 30 children were selected from a public school of Caratateua island in Para state. 20 children were female and 10 were male. The result indicated that 83% of children are classified as medium level and 17% as poor level. The average of chronological ages among all analyzed children is 9,5 years old, the equivalent age for locomotion skills is 7,56 years old and the equivalent age for objects control skills is 9,65 years old. The average for objects control skills was superior than locomotion skills. Then, the obtained results permit us to suggest that each age group has a prívate way to acquire motor skills, that's why each one needs to be adequately stimulated in a global way (educational and familiar atmosphere, biologically and tasks). In this context, stand out the importance of an instrument of mensuration of the development to support the planning of a structured intervention in the real needs of the students.
Keywords: motor valuation; motor skills; childish development